Pea, Bee, & Jay. Book 4, Farm feud - Smith, Brian (Comic book writer) (New York : Harper Alley, 2022)
With their friendship on the line after a huge fight, Pee and Bee search for new friends, while Jay takes matters into his own wings to bring them all back together.
2.5
K-3.
Keywords: Peas -- Comic books, strips, etc -- Juvenile fiction; Bees -- Comic books, strips, etc -- Juvenile fiction; Birds -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Comic books, strips, etc -- Juvenile fiction; Interpersonal relations -- Comic books, strips, etc -- Juvenile fiction; Humorous stories; Peas -- Fiction; Bees -- Fiction; Birds -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Humorous stories; Cartoons and comics; Funny animal comics; Humorous comics; Graphic novels; Comics (Graphic works)